2015
DOI: 10.3390/ijms16059896
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Maltose-Binding Protein Induces M1 Polarity of RAW264.7 Macrophage Cells via a TLR2- and TLR4-Dependent Manner

Abstract: Maltose-binding protein (MBP) is a critical player of the maltose/maltodextrin transport system in Escherichia coli. Our previous studies have revealed that MBP nonspecifically induces T helper type 1 (Th1) cell activation and activates peritoneal macrophages obtained from mouse. In the present study, we reported a direct stimulatory effect of MBP on RAW264.7 cells, a murine macrophage cell line. When stimulated with MBP, the production of nitric oxide (NO), IL-1β, IL-6 and IL-12p70, and the expressions of CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The inflammation associated with disease can be driven by allergic or non‐allergic mechanisms, where the activation of Toll‐like receptors (TLRs) on epithelial cells and macrophages regulates the initial nature of the innate inflammatory response . TLR4 activation in response to bacterial components, such as lipopolysaccharide (LPS), will drive nuclear factor (NF)‐κB‐driven inflammatory programming towards IL‐1β, IL‐6, and TNF‐α production in macrophages, promoting the activity of type 1 (M1)‐resident populations and neutrophilic inflammation. Conversely, stimulation of the IL‐4 receptor will result in STAT6 activation, which promotes the development of type 2 (M2)‐resident macrophage populations.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammation associated with disease can be driven by allergic or non‐allergic mechanisms, where the activation of Toll‐like receptors (TLRs) on epithelial cells and macrophages regulates the initial nature of the innate inflammatory response . TLR4 activation in response to bacterial components, such as lipopolysaccharide (LPS), will drive nuclear factor (NF)‐κB‐driven inflammatory programming towards IL‐1β, IL‐6, and TNF‐α production in macrophages, promoting the activity of type 1 (M1)‐resident populations and neutrophilic inflammation. Conversely, stimulation of the IL‐4 receptor will result in STAT6 activation, which promotes the development of type 2 (M2)‐resident macrophage populations.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were treated with various concentrations of sample extracts in the presence of LPS (1 μg/mL) for 24 h at 37 °C with 5% CO 2 . Subsequently, the culture supernatant was assayed according to the manufacturer’s instructions [ 9 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using a polymyxin B-agarose column (Sigma-Aldrich, Saint Louis, MO, USA), the endotoxin in the MBP protein was removed using ultrafiltration techniques with Amicon Ultra-15 Centrifugal Filter Units plus Ultracel-10 (Merck Millipore, Billerica, MA, USA). The residual endotoxin level in the MBP protein was examined with a limulus amebocyte lysate-based kit (BioWhittaker, Atlanta, GA, USA) [ 12 , 13 ]. The level of endotoxin in the MBP protein prepared for the experiments was less than 0.05 EU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, TLRs are the most widely studied family of PRRs (pattern recognition receptors) on professional phagocytes such as macrophages and DCs [ 10 , 11 ]. Other studies found that MBP directly induced macrophage activation and M1 polarization through the TLR2 and TLR4 signaling pathways [ 12 , 13 ]. Our latest studies showed that Th1 polarization and TLR2/TLR4/TLR9 activation were synergistically induced by the combination of MBP and BCG and were the first to reveal that the cross-talk between TLR signaling pathways was associated with the activation of Th1 cells by the combination of MBP and BCG [ 14 ].…”
Section: Introductionmentioning
confidence: 99%